2018
DOI: 10.14382/epitoanyag-jsbcm.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of firing temperature on triaxial electrical porcelain properties made from Tanzania locally sourced ceramic raw materials

Abstract: The study has investigated the effect of firing temperature during the production of technical triaxial electrical porcelain, for electrical insulation applications using Tanzania locally sourced ceramic raw materials. The green triaxial porcelain samples containing 50 wt% of Pugu kaolin, 35 wt% of Same clay and 15 wt% of feldspar were produced and fired at 1200°C-1300°C with a heating rate of 10°C/min (dwell time of 1.5h) and cooled at 10 0 C/min to a room temperature. X-ray diffraction technique was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…6d, the dielectric strength of porcelain insulators were found to increase with increasing firing temperature and reaches a maximum of 8 kv/mm at a firing temperature of 1300 °C. The increasing of the dielectric strength may be due to increased vitrification range of the electrical porcelain samples at the optimized firing temperature (Ngayakamo and Park, 2018). Among the desired batch composition, the dielectric strength of batch-2, batch -3 and batch- 4 found to fall in the specified range of 6.1–13 kv/mm for porcelain insulator (Olupot et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6d, the dielectric strength of porcelain insulators were found to increase with increasing firing temperature and reaches a maximum of 8 kv/mm at a firing temperature of 1300 °C. The increasing of the dielectric strength may be due to increased vitrification range of the electrical porcelain samples at the optimized firing temperature (Ngayakamo and Park, 2018). Among the desired batch composition, the dielectric strength of batch-2, batch -3 and batch- 4 found to fall in the specified range of 6.1–13 kv/mm for porcelain insulator (Olupot et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The quality and quantity of the raw materials plays a significant role on the properties of blended green body and the fired body/microstructure of porcelain body that ultimately affect the performance of electrical porcelain insulators. The clay [Al 2 Si 2 O 5 (OH) 4 ] content when wet, acts as a binder for the other body ingredients in the green state which confirm plasticity of the body for easy molding and shaping, while feldspar [K x Na 1-x (AlSi 3 )O 8 ] serve as flux and alternative source of alumina and silica, whereas quartz (SiO 2 ) used as a filler material helps to maintain the shape of porcelain body at green state and during firing (Ngayakamo and Park, 2018). Various scholars designed efficient high quality porcelain insulator using ball clay as a plastic materials (Anih et al., 2005; Oladiji et al., 2010).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, the siliceous porcelains with density values ranging from 2.20 to 2.40 g/cm 3 are appropriated to be used as low-voltage insulators 20,21 . The results also showed that the porcelain specimens with higher amount of firewood ash waste (4.20 wt.%) in the composition had lower apparent density, which may be due to the closed porosity caused by the formation of gas bubbles inside them [22][23][24] . This result indicates that the replacement of sodium feldspar with firewood ash waste in electrical siliceous porcelain formulations is limited.…”
Section: Resultsmentioning
confidence: 92%
“…This suggests that the possibility of electric shock is low since the insulator has a good charge storage capacity. The samples exhibit electrical resistance that are above the recommended range 1.0x10 6 which is a quality of a good insulator [3,54]. Generally, this suggests that the fine nature of the talc powder helped to amplify the qualities of the other constituents in the porcelain insulators.…”
Section: Tablementioning
confidence: 99%